The Effectiveness of QRIS Transaction Implementation During the COVID-19 Pandemic - Sendjaja, Theodorus; Rachbini, Didik J.; Astini, Rina; Asih, Daru (International Journal of Science and Society, 2023)
The Covid-19 pandemic has hit the entire world, including Indonesia, causing severe impacts on the social and economic sectors. Electronic or non-cash money payment systems have progressed along with the development of information technology, in line with the increase in users and service providers of electronic money payment systems. This study aims to analyze the effectiveness of QRIS transaction implementation during the Covid-19 pandemic. Qualitative research is used to bring researchers closer to the phenomenon studied, especially in the context of using QRIS by micro, small and medium enterprises (MSMEs) engaged in food sales. Based on the results of the analysis that has been conducted, the impact of implementing QRIS during the Covid-19 pandemic is as follows: 1) At first, many merchants and the general public did not fully understand the features and benefits of the QRIS program. Hence, the installation of QRIS-based payment gateways for merchant transactions still experienced obstacles. The use of QRIS has not become common because many individuals still do not have an application to carry out these transactions, and sometimes problems related to QR code inaccuracies also become obstacles. 2) Some MSME merchants agree to use QRIS as a payment method because it is more economical and helps reduce the risk of spreading Covid-19. 3) One of the main advantages of using QRIS is the very low transaction fee, only one rupiah. The use of QRIS also provides convenience because it does not require large amounts of cash, and transactions can be completed quickly and safely without the need to carry cash. In addition, no physical interaction is required, which helps reduce the risk of spreading Covid-19. However, there are several disadvantages to using QRIS, including a limit on the number of transactions of up to 2 million rupiah and problems with an unstable internet connection that can limit the use of this system. This shortage may be unavoidable because using QRIS requires internet access and quota for transactions, and there can also be inventory problems in stores.